PENEGAKAN HUKUM TERHADAP PENYELUNDUPAN ROKOK DAN MINUMAN KERAS OLEH PENYIDIK PEGAWAI NEGERI SIPIL BEA CUKAI SELAT PANJANG BERDASARKAN UNDANG-UNDANG NOMOR 39 TAHUN 2007 TENTANG CUKAI - Khairani, Annisa Dwi; Indra, Mexsasai (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Goods import export activities in the form of customs and excise goods become one of the activities that is always done in every country in the world. However, such activities can also be used as the best use of an illegal act of smuggling. Strait Panjang becomes a strategic place to smuggle goods such as cigarettes and liquor, smugglers can be imposed criminal penalties based on Law Number 39 Year 2007 About Excise.The purpose of writing this thesis, namely to know: First, the law enforcement of smuggling of cigarettes and liquor by the investigator civil servants long strait customs based on the law number 39 of 2007 on excise, Both barriers law enforcement against smuggling of cigarettes and liquor by the investigator Civil servants of the long strait customs under Act No. 39 of 2007 on excise, Third attempt made in overcoming law enforcement inhibiting the smuggling of cigarettes and liquors by the investigators of long-strait customs civil servants under the law number 39 years 2007 on excise duty. This type of research is a sociological study looking at the correlation between law and society, using interview method in Customs Strait Long.From the results of research based on three formulation problems can be concluded, First Law enforcement against smuggling of cigarettes and liquor has not run with the maximum because all the perpetrators fled. Second, law enforcement obstacles to smuggling of cigarettes and liquor are the lack of personnel and investigators of long-strait customs civil servants, lack of socialization with the public, the number of small ports. Third, the efforts undertaken in overcoming law enforcement inhibiting the smuggling of cigarettes and liquor is to improve coordination with other law enforcement officers, provide counseling and cooperate with communities, and improve oversight of small ports.Keywords: Law Enforcement-Cigarettes and Liquor-Customs